Ethnicity and social work practice - Cox, Carole B. (Oxford University Press, 1998)
Ethnicity and Social Work Practice fills a major gap in the literature on social work and ethnicity by offering a broad, conceptual model applicable to all ethnic populations. It presents ethnicity in an innovative way, focusing on its many dimensions as encountered in various areas of social work practice (individuals, families, groups, and communities) and includes separate chapters on social services, healthcare, and social planning and policy development. Rather than attempting to address these issues by describing the traits of specific ethnic groups, this text presents the model of an ethnic lens. It is through this lens that ethnic groups are likely to perceive society, problems, the helping process, and the social workers who assist them. At the same time, social work practitioners perceive various ethnic groups through their own lenses, based upon their own experiences and beliefs. The effectiveness of practice and the establishment of a valid social work relationship depends to a large extent on the clarity of these lenses